Legal Regulation of the Agreement on Provision of Tourist Services during the Pandemic Covid-19 - LYTVYN, Stepan; ZINCHENKO, Olena; BASARAB, Olha; GONCHARUK, Valentyna; ANDRUSIV, Uliana; RYZHUK, Iryna (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.12.2(50).18, 2021)
The article is devoted to the content of legal instruments in terms of tourism business, namely the problems of legal regulation of the contract for the provision of tourist services. The analysis of the state of development of this problem shows that the issue of legal regulation of contractual relations in general and the contract in tourist services in general is insufficiently studied. This is due to various factors, including the fact that constant integration processes to the international community force Ukraine to adjust its domestic legislation in accordance with international requirements, but these measures are often inconsistent or incomplete, so there are many contradictions in modern Ukrainian civil law. The author's vision of the content of the package of measures that can positively influence not only the development of the tourism industry in general, but primarily to help identify those legal segments that need improvement in the future.